Study of Heavy Metals Concentration on the Main Rivers from Valcea Area, Romania - BARBU, CRISTINA; PREDA, ANISOARA; GHITULESCU, ALINA; POPESCU, ALEXANDRU; PETRE, EMIL; SENDRESCU, DORIN; BRANESCU, VALENTIN (Asian Journal of Chemistry, 2010)
This paper presents a study of a few heavy metals e.g., iron, manganese, copper, chromium and zinc from 5 rivers (Olt, Lotru, Oltet and Topolog river) of hydrographic Valcea area. The concentration of cations was determined by atomic absorption spectrometry.